Investigation on biochemical, colicinogenic and mannose resistant hemagglutination characteristics of e. coli strains isolated from healthy and diarrhoeic lambs - Mehmet Çorlu (Eurasian Journal of Veterinary Sciences)
In this study, biochemical, colicinogenic, hemagglutination (HA), mannose sensitive hemagglutination (MSHA) and mannose resistant hemagglutination (MRHA) characteristics of 200 E. coli strains isolated from neonatal healthy and diseased lambs have been examined. There was no significant differences as to the biochemical characteristics of the strains isolated from healthy and diarrhoeic lambs. No htmolitic activity was found in all isolates. In HA tests, using different species of erytrocytes (human, bovine, chicken, guinae-pig and ovine) multiple HA patterns were observed. MRHA, MSHA and HA ( —) rates of the organisms originated from healthy and diseased lambs, were found to be 28 %-32 % for MRHA, 27 %—31 % for MSHA and 45 % — 37 %for HA ( — ). There was not significant differences in MRHA, MSHA and HA ( —) characteristics of two groups. While 10 % of E. coli strains isolated from healthy lambs was colicinogenic, 13 % of them was isolated from diseased lambs.